2012
DOI: 10.1088/0004-637x/753/2/120
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Flows in Cool-Core Galaxy Clusters

Abstract: We argue that bulk spiral flows are ubiquitous in the cool cores (CCs) of clusters and groups of galaxies. Such flows are gauged by spiral features in the thermal and chemical properties of the intracluster medium, by the multiphase properties of CCs, and by X-ray edges known as cold fronts. We analytically show that observations of piecewise-spiral fronts impose strong constraints on the CC, implying the presence of a cold, fast flow, which propagates below a hot, slow inflow, separated by a slowly rotating, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 64 publications
2
26
0
Order By: Relevance
“…Such bubble entrainment was previously suggested by Keshet (2012). Future numerical simulations, that include both jet inflated bubbles and sloshing, will test this possible interpretation.…”
Section: Amplified Magnetic Fields Underneath the Cold Frontsupporting
confidence: 61%
“…Such bubble entrainment was previously suggested by Keshet (2012). Future numerical simulations, that include both jet inflated bubbles and sloshing, will test this possible interpretation.…”
Section: Amplified Magnetic Fields Underneath the Cold Frontsupporting
confidence: 61%
“…A realistic spiral flow simulation, incorporating the physical processes outlined above, would directly test our approximation of two-phases composing the spiral, and gauge the simplified power-law scalings we derive. Simulations and observations would also test additional predictions of the model, such as the presence of a convective zone, a CF intermittency, and entrained radio bubbles (Keshet 2012). The role of the spiral flow in regulating the universal profile will be ruled out if Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Simulations also show that there is a general radial expansion of the cold fronts away from the cluster potential minimum (Roediger et al 2011). Keshet (2012) demonstrated that such expanding, spiral flows must have a "bulging" cylindrical or "open barrel" shape as seen from lines of sight parallel to the sloshing plane. viscid simulation at an epoch t ∼ 1.6 Gyr past the core passage.…”
Section: Velocity Moment Mapsmentioning
confidence: 90%